The Physics of Electric Saroj Veena: A Folk Musical Instrument from India's North Eastern Region - SARKAR, JOYANTA (Research Journal in Advanced Humanities, 2023)
Saroj Veena is known as a famous Folk musical Instrument in the North eastern part of India. We will discuss about the Shape and Size, Structure, body mechanism of Saroj Veena. In our lab studies, we look at the harmonic structure of standing waves in Saroj Veena strings. Using a digital oscilloscope with a Fast Fourier transform and a magnetic pickup from a Saroj Veena, the experimental data was gathered. Depending on where the string is plucked, the harmonic amplitudes in the measured signal vary, giving the sound a distinct timbre. The relative amplitudes of transverse standing waves in a string were determined from experimental data and predicted by the wave equation when the boundary and beginning circumstances matched the initial shape of the string.